2007
DOI: 10.1590/s0100-204x2007000900009
|View full text |Cite
|
Sign up to set email alerts
|

Uso industrial de grãos de cevada de lavouras dessecadas em pré-colheita

Abstract: Resumo -O objetivo deste trabalho foi avaliar o impacto da antecipação da colheita de lavouras de cevada sobre a germinação dos grãos, ao longo de 12 meses de armazenamento. O ensaio de campo foi realizado em 2002 e 2003. As parcelas colhidas foram armazenadas nos anos subseqüentes aos dos ensaios em campo, e a germinação foi monitorada mensalmente. Os tratamentos avaliados foram: dessecação com os princípios ativos glifosato e paraquat, nas doses 1, 1,5 e 2 L ha -1 , além das testemunhas, colhidas normalmente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…High moisture in the inner layers of the seed activate germination and deterioration processes, and reduce the physiological quality of the seeds (Peske et al, 2012). Similar results were obtained by Caierão and Acosta (2007), in which early harvest of barley of treatments with glyphosate and paraquat applied for preharvest desiccation favored the qualitative maintenance of the seeds in relation to the treatment without chemical desiccation. Germination of the wheat seeds changed according to the herbicide and the application rate (Table 5).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…High moisture in the inner layers of the seed activate germination and deterioration processes, and reduce the physiological quality of the seeds (Peske et al, 2012). Similar results were obtained by Caierão and Acosta (2007), in which early harvest of barley of treatments with glyphosate and paraquat applied for preharvest desiccation favored the qualitative maintenance of the seeds in relation to the treatment without chemical desiccation. Germination of the wheat seeds changed according to the herbicide and the application rate (Table 5).…”
Section: Resultssupporting
confidence: 83%
“…differ between the herbicides; however, they were superior to the control. Preharvest desiccation provides for qualitative maintenance of seeds compared to treatments without desiccation (Caierão and Acosta, 2007). In application in the soft dough to hard dough stage, final germination was higher in the treatment with glufosinate than in the control or 2,4-D+glyphosate treatment in the first and second harvest (Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…However, Caierão and Acosta (2007), when using paraquat and glyphosate on barley crops, observed no negative interference of the desiccants on seed vigor. It should be emphasized that the values obtained in the germination test, in the present study, allow the seeds obtained -only where the treatment was desiccated with glyphosate at stage 11.2 -to be rated as suitable for sale because according to Normative Instruction No.…”
Section: Resultsmentioning
confidence: 88%
“…These results differ from those obtained by Kappes et al (2009), where the application of diquat resulted in a lower percentage of normal soybean seedlings in the cold tests. Caierão and Acosta (2007) concluded that the use of glyphosate did not affect the germination of barley seeds. In relation to the accelerated aging test (Table 7), all treatments presented higher results in the second application period with the additional control, followed by paraquat + diuron, diquat and glufosinate ammonium.…”
Section: IIImentioning
confidence: 98%